Il problema della colpa: Die Schuldfrage e I sommersi e i salvati. La riflessione di Karl Jaspers e di Primo Levi (Materiali di Estetica. Terza serie, 2025)
In 1946, the philosopher Karl Jaspers appealed to Germany to help it assume its own guilt, indicated as criminal, political, moral and metaphysical guilt. For the first two, a court is competent (for the political one it was Nuremberg); for moral guilt, the individual conscience is competent, which does not make concessions: crimes remain such even if ordered. For the survivor of the Shoah who feels the (metaphysical) guilt of being alive in someone else's place, only God is competent. Primo Levi helps us understand the meaning.
Keywords: legal-political guilt; moral; metaphysics